Enhancing nitorgen availability using compost and clinoptilolite zeolite - Haruna, Ahmed Osumanu; Omar, Latifah; Ab. Majid Ahmed, Nik Muhamad (Universiti Putra Malaysia Press, 2017)
This book provides information on soil nitrogen forms and their availability in a tropical soils. It also discusses how the productivity of crops is affected by nitrogen availability. The significance of soil nitrogen pool, an approach for improving soil nitrogen availability, factors affecting its availability in acid soils, and the effects of clinoptilolite zeolite and organic amendments derived from agricultural wastes on soil nitrogen is highlighted in this book. Included are findings of a series of laboratory assessment, pot experiment, and field trials carried out to evaluate the effectiveness of co-application of inorganic fertilizers, clinoptilolite, and organic amendments in enhancing soil nitrogen availability for crop uptake and yield. In many ways this book will help facilitate agronomists, environmentalists, research scientists, farmers, students, fertilizer makers, and others in their work.